2,6-Bis(5,6-diisopropyl-1,2,4-triazin-3-yl)pyridine: a highly selective N-donor ligand studied by TRLFS, liquid-liquid extraction and molecular dynamics - Beele, Björn B.; Skerencak-Frech, Andrej; Stein, Arnulf; Trumm, Michael; Wilden, Andreas; Lange, Steve; Modolo, Giuseppe; Müllich, Udo; Schimmelpfennig, Bernd; Geist, Andreas; Panak, Petra (New journal of chemistry, 2016)
The complexation of Cm(III) and Eu(III) with 2,6-bis(5,6-di-i-propyl-1,2,4-triazin-3-yl)-pyridine (iPr-BTP) is studied in methanol : water (1 : 1, vol) by time-resolved laser-induced fluorescence spectroscopy (TRLFS). With increasing ligand concentration [Cm(iPr-BTP)3]3+ and [Eu(iPr-BTP)3]3+ are formed, respectively. Stability constants of log β3′([Cm(iPr-BTP)3]3+) = 16.3 ± 0.3 and log β3′([Eu(iPr-BTP)3]3+) = 14.9 ± 0.3 are determined. Thermodynamic data of the complexation reactions is obtained in a temperature range of 20-60 °C. The complexation of iPr-BTP with both metal ions is exothermic (Cm(III): ΔrH3′ = −(64.1 ± 3.0) kJ mol−1; Eu(III): ΔrH3′ = −(42.6 ± 2.0) kJ mol−1). The reaction entropy for the formation of [Eu(iPr-BTP)3]3+ is higher compared to the Cm(III) complex (Cm(III): ΔrS3′ = (96.5 ± 6.5) J mol−1 K−1; Eu(III): ΔrS3′ = (136.0 ± 15.2) J mol−1 K−1). Different complexation entropies for the formation of [Cm(iPr-BTP)3] and [Cm(nPr-BTP)3] are explained by molecular dynamics simulations. Results from liquid-liquid extraction tests confirm the ligand's peculiar extraction kinetics observed in previous studies and link them to the thermodynamic data.
Gesehen am 05.05.2020